2019
DOI: 10.1111/jdv.15953
|View full text |Cite
|
Sign up to set email alerts
|

Nodular skin lesions: correlation of reflectance confocal microscopy and optical coherence tomography features

Abstract: Background Nodular lesions have common clinical appearance but different prognoses. Differential diagnosis between melanoma (MM), basal cell carcinoma (BCC) and dermal naevus (DN) poses a challenge in clinical practice. Reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) are promising non-invasive imaging techniques, potentially able to decrease redundant biopsies. RCM allows in vivo visualization of skin down to the papillary dermis at almost histological resolution, while OCT, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 34 publications
(56 reference statements)
1
29
2
Order By: Relevance
“…In a recent study, Garbarino et al used the combination of RCM and OCT to diagnose nodular skin lesions 18 . Interestingly, they found that epidermis icicle shape in OCT images significantly paralleled cerebriform nests in RCM images of MM 18 . In our study, the MSOT data rendering spatial distribution of melanin and vascularization indicated that all skin tags were benign, since there was no infiltration of vessels inside the melanin signal from the lesions 28 .…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In a recent study, Garbarino et al used the combination of RCM and OCT to diagnose nodular skin lesions 18 . Interestingly, they found that epidermis icicle shape in OCT images significantly paralleled cerebriform nests in RCM images of MM 18 . In our study, the MSOT data rendering spatial distribution of melanin and vascularization indicated that all skin tags were benign, since there was no infiltration of vessels inside the melanin signal from the lesions 28 .…”
Section: Discussionsupporting
confidence: 56%
“…In a recent study, Garbarino et al used the combination of RCM and OCT to diagnose nodular skin lesions 18 . Interestingly, they found that epidermis icicle shape in OCT images significantly paralleled cerebriform nests in RCM images of MM 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliable correlates for epidermal and junctional histological features, useful for diagnostic purposes, were identifiable using RCM imaging (18,20,24,25,30). Four melanoma scoring algorithms based on these features were validated in literature (18,27,83,84).…”
Section: Optical Imagingmentioning
confidence: 99%